Guideline for food system profile development at sub-national levels in Ethiopia - Ethiopian Public Health Institute (EPHI); Food and Nutrition Society of Ethiopia (FoNSE); Bioversity International and the International Center for Tropical Agriculture (2025)
Ethiopia has developed and endorsed a federal-level Food System Transformation Roadmap in 2021. Since successful implementation requires the full awareness, dedication, and engagement of all administrative regions in Ethiopia, the roadmap is currently being cascaded down to the subnational levels. Accordingly, it is very important to engage the various governmental and non-governmental organizations and other stakeholders (including the private sector) operating in the respective regions by equipping them with adequate knowledge, awareness, and capacities to make informed decisions. It is also important to create opportunities for diverse stakeholders to actively participate in collaborative platforms. To ensure successful transformation towards the desired goals at regional levels, the relevant stakeholders need to have a clear understanding of the status of food systems in general and with their own engagement areas in particular. Therefore, developing knowledge products, tools, and processes (e.g., food system profiles, food system dashboards, etc.) is crucial to help regional stakeholders, especially government officials, map their roles, analyze sectoral trends (if any), assess local food systems holistically, and further prioritize actions to effectively navigate food systems transformation, either by integrating existing programmes and projects or by developing new initiatives. This comprehensive food system profile development guideline supports regional authorities to co-develop food system profiles that highlight key aspects of the local food system, such as notable features, trends, accomplishments, and challenges of each food system component through identifying and prioritizing key indicators. The guideline for food system profile development at regional level is built based on the experience from the Amhara region food systems profile development. The guideline is designed to be flexible and adaptable, enabling various actors to customize approaches according to different local priorities, conditions, and stakeholder dynamics. The current version of the guideline has been refined with inputs from experts across various sectors. However, as the concepts and approaches of food systems and food system profiling process are relatively new, we welcome ongoing feedback and collaboration to improve the guideline during the Food System Roadmap implementation towards 2030.